LINGUISTIC INTERFERENCE OF THE NATIVE LANGUAGE IN THE ACQUISITION OF ENGLISH GRAMMATICAL STRUCTURES - Diana Komilovna Ruzmetova (Western European Studies, 2025)
Grammatical interference, or negative transfer, remains a persistent challenge in English as a Second Language (ESL) acquisition, particularly when learners apply syntactic and morphological rules from their native language (L1) to English. This study offers a qualitative-descriptive synthesis of empirical and theoretical research examining the nature, causes, and pedagogical implications of L1-induced grammatical errors among ESL learners. Drawing on contrastive analysis theory and interlanguage theory, the paper categorizes common interference patterns in morphology (e.g., tense inflection, pluralization, article usage) and syntax (e.g., word order, negation, modifier placement). The findings indicate that interference is systematic and strongly influenced by the typological distance between L1 and English. Errors are especially pronounced in areas where learners’ native languages lack grammatical equivalents found in English. While such errors often persist over time, they can be mitigated through targeted instructional interventions. Effective strategies include contrastive grammar instruction, metalinguistic awareness activities, timely corrective feedback, and the use of learner corpora for tailored error analysis. The study emphasizes the importance of aligning grammar instruction with learners’ linguistic backgrounds and advocates for more responsive and individualized pedagogical approaches. It concludes by recommending further longitudinal research and enhanced teacher training to support grammar instruction in multilingual ESL contexts
Keywords: grammatical interference; negative transfer; ESL